Frost Characterization for the Altiplano, Valleys and Chaco Regions of Bolivia - Torrez, Guillermina Miranda (Archives of Business Research, 2024)
The analysis focused on frost events in the Altiplano, Valles, and Chaco regions of Bolivia, with an emphasis on sub-zero temperatures and related atmospheric patterns to identify the predominant type of frost. A retrospective, observational, and longitudinal design was employed to analyze minimum temperatures from nine meteorological stations between 2005 and 2019. Radiative frosts in the Altiplano showed stability in minimum temperatures from April to October, with low variability and the absence of outliers, while variability was higher in the Valles and Chaco regions. Frost events were more frequent and severe from May to August, with the Altiplano being the most affected region. Satellite imagery and atmospheric reanalysis data from 2010 to 2019 were used for the visual interpretation of atmospheric patterns. A mixed-method approach—quantitative for the statistical analysis of minimum temperatures and qualitative for image interpretation—identified 24 advection frost events between 2010 and 2019, primarily in July and August, associated with high-pressure systems over the Atlantic and Pacific. The Chaco region was the most affected by advection frosts, followed by the Altiplano and the Valles. These findings underscore the importance of spatial and temporal variability in frost occurrence and the need for regional strategies to manage climate risk. It is concluded that altitude, along with factors such as solar radiation, thermal inversion, and wind, is key in frost formation, with radiative frosts being the most common, although advection frosts are also significant, especially under cold front conditions.